CRYSTAL CHEMISTRY OF URANYL MOLYBDRATES. IX. A NOVEL URANYL MOLYBDATE SHEET IN THE STRUCTURE OF TL2[(UO2 )2O(MOO5)] - Krivovichev S.V.; Burns P.C. (My University, 2003)
Crystals of a new thallium uranyl molybdate, Tl-2[(UO2)(2)O(MoO5)], have been synthesized by high-temperature solid-state reactions. The structure [monoclinic, P2(1)/n, a 8.2527(3), b 28.5081(12), c 9.1555(4)Angstrom, beta 104.122(1)degrees, V 2088.91(15) Angstrom(3), Z = 8] was solved by direct methods and refined to R1 = 0.039 (wR2 = 0.081) on the basis of 8609 unique reflections. The structure is novel in that Mo6+ cations occur in both tetragonal pyramidal and trigonal bipyramidal coordination environments, and it contains a uranyl molybdate sheet of composition [(UO2)(2)O(MoO5)] with more uranium than molybdenum. The uranyl molybdate sheets are composed of UrO(5) (Ur: uranyl ion, UO22+) pentagonal bipyramids and MoO5 polyhedra that are linked by the sharing of edges. Within the sheet, eight UrO(5) bipyramids share edges, resulting in a Z-shaped complex that is oriented approximately parallel to [010]. The MoO5 polyhedra each contain one O atom that is not shared within the sheet; these are oriented both up and down relative to the plane of the sheet. The anion topology of the sheet consists of pentagons, squares and triangles. In the sheet, all pentagons are populated by U, four-fifths of the squares contain Mo, and the triangles are empty. The uranyl molybdate sheets are parallel to ((1) over bar 01) and are linked via Tl+ cations located in the interlayer.
Keywords: uranyl molybdate; thallium; crystal structure